THE IMPORTANT OF NEUROPHYSIOLOGY EXAMINATION IN DIAGNOSING SEGMENTAL ZOSTER PARESIS: CASE REPORT - Eric Hartono Tedyanto; Ni Made Dwita Pratiwi; I Komang Arimbawa; I Putu Eka Widyadharma (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Segmental zoster paresis (SZP) is a very uncommon complication characterized by localized weakening of the upper or lower limbs. Case report: A 69-year-old man came with complaints of weakness in the right leg two months ago. He had weakness in his right leg after two days of having herpes on his right leg. There was paresthesia and hypesthesia on neurological examination according to the L1-L3 dermatome. Neurophysiology examination revealed a neuropathy in the right femoral nerve. Discussion: Varicella-zoster virus, being a neurotrophic virus, primarily invades and incubates in the dorsal root or cerebral ganglion nerve cells. Etiological investigations in SZP patients have revealed that the anterior root is the most prevalent location of inflammation and degeneration. Conclusion: SZP is a rare complication following VZV infection that can lead to misdiagnosis and overtreatment in clinical practice. The neurophysiological examination is very important in diagnosing segmental zoster paresis.